Efektivitas Agen Pendeplesi GSH pada Sitotoksisitas Cisplatin terhadap Sel Kanker: Systematic Literature Review - Elisa Tri Oktaviyana; Wahyu Utami (Pharmacon: Jurnal Farmasi Indonesia, 2021)
Cisplatin is one of chemotherapy agent for long cancer, ovarium cancer, gastric cancer, breast cancer, head-neck cancer. However, in the fact, the role of cisplatin does not always provide an optimal effect because it often appears cancer cell resistance phenomenon to cisplatin. This resistance condition occurs partly due to the inactive metabolite cause of conjugation reaction between cisplatin and GSH in cancer cells. Therefore, gluthathione (GSH) has an important role in controlling cisplatin resistance. This study aims to analyze some combination of cisplatin and the depletion agent of gluthathione (GSH) as a support for cisplatin activity in several types of cancer cells within in vitro scope. This study is prepared using systematic literature review method. Library search were carried out on two accredited international journals databases, namely PubMed and Science Direct with interval years of publication in 2011-2020. From 10 selected journals, it was shown that the use of GSH depletion agents could enhance the cytotoxic effect of cisplatin. This was analyzed based on data of the number measured GSH cells and the number of living cells (% cell viability) which gave a significant decrease. The result of research are expected to be able to provide information for the development of therapeutic agents on cisplatin as chemotherapy.